The same, but not exactly: Towards a subversion and resignification of the discursive format of Ricardo Palma’s traditions in Clorinda Matto de Turner’s Tradiciones cuzqueñas (1884-1886) - Mori, José (2022)
In this paper, we are interested in reflecting on how the mimetic procedure of Ricardo Palma’s Tradiciones peruanas is carried out in Clorinda Matto de Turner’s Tradiciones cuzqueñas (1886). Specifically, we will focus on the analysis of the stories «Un centinela de acero» and «Ccata hueqque», by the Cusquenian writer. For this purpose, we will assume a multidisciplinary approach based on the concepts of two authors: Homi Bhabha’s mimesis, from a rhetorical perspective, and the framing of memory, developed by Michael Pollak. It is argued that Clorinda Matto de Turner appropriates the genre of «tradition» to redefine it and establish an aesthetic-ideological position opposed to that of Ricardo Palma. From this, she resignifies the genre to express the unspoken through a new representation of the past concerning the present and the indigenous cultural other. It is concluded, then, that the two abovementioned stories imply an ideological operation that opposes the national imaginary that Palma constructs in his stories.